THE EFFECTIVENESS OF GUIDANCE AND SUPERVISION OVER HALAL FOOD PRODUCT BASED ON THE QANUN ACEH NUMBER 8 OF 2016 CONCERNING HALAL PRODUCT GUARANTEE SYSTEM - Azrianda, Melvi Salsabil; Yani, Teuku Ahmad; Gani, Iskandar A (Jurisdictie: Jurnal Hukum dan Syariah, 2021)
Qanun Number 8 of 2016 regulates the Halal Product Guarantee System, but there are still many business actors in Banda Aceh who do not have halal certificate for the food they sell. This journal aims to further examine the protection for Muslim consumers regarding food products or places of business that do not have a halal certificate and logo given by LPPOM Aceh and to find out the effectiveness of LPPOM MPU Aceh in providing guidance and supervision over food products distributed in Aceh. The method and type of writing is empirical-legal by conducting interviews with the Aceh MPU LPPOM. This writing approach is known as an empirical socio-legal study. Based on the research results, the legal protection for Muslim consumers regarding food products or places of business that do not have a halal certificate and logo is regulated in the Qanun SJPH. The inclusion of the halal logo is mandatory. However, there are business actors who still have not applied to obtain halal certification. This happened because LPPOM experienced obstacles in terms of guidance and supervision over halal food sold in Aceh and the absence of regulations concerning the Qanun SJPH implementation.Qanun Nomor 8 Tahun 2016 bertuliskan tentang Sistem jaminan Produk Halal, namun masih banyak pelaku usaha makanan di Banda Aceh yang tidak melakukan sertifikasi makanan halal terhadap makanan yang dijual. Tujuan penulisan jurnal ini adalah untuk mengkaji lebih lanjut terhadap perlindungan konsumen muslim pada produk atau tempat usaha makanan yang tidak memiliki sertifikat dan logoÂ halal LPPOM Aceh efektivitas LPPOM MPU Aceh dalam melakukan pembinaan dan pengawasan terhadap produk makanan yang beredar di Aceh. Metode dan jenis penulisan ini bersifat yuridis empiris dengan melakukan wawancara kepada pihak LPPOM MPU Aceh. Pendekatan penulisan ini disebut dengan penelitian empirik dan hukum sosiologis. Berdasarkan hasil penelitian Perlindungan hukum konsumen muslim terhadap produk atau tempat usaha makanan yang tidak memiliki sertifikat dan logo halal di atur dalam Qanun SJPH. Pencantuman logo halal bersifat wajib. Namun kenyataannya masih ditemukan pelaku.usaha yang belum melakukan sertifikasi.halal. Hal tersebut terjadi karena LPPOMI mengalami hambatan dalam hal pembinaan dan pengawasan. terhadap makanan halal. yang beredar di Aceh dan tidak adanya peraturan pelaksana Qanun SJPH.